Construction of cubature formula for double integration with algebraic singularity by spline polynomial - Bichi S.L.; Eshkuvatov Z.K.; Long N.M.A.N.; Ismail F. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus/WOS